Reflective Simulation for On-Line Workload Planning and Control - Revetria, R.; Tonelli, F. (2007 Winter Simulation Conference, 2007)
Since its beginning, simulation has been used to study complex systems in order to infer on their future behavior, in this field several applications have been made using it as off-line tool for strategic level choices. In modern application, especially in the field of industrial automation, on-line simulation has been extensively used for supporting operative decision trough a classical schedule- simulate loop. The paper presents an application of on-line simulation to the distribution logistics sector: a department store is here controlled by on-line simulators able to help decision maker to decide how many counters to kept opened or how many people to use for shelves replenishment. Since this exercise could seriously affect the performances of a real life department store, the methodology is, in fact, very sensible to parameter settings, a nested simulator has been implemented and used for algorithm fine tuning and critical parameter choice.